Maxillary Growth after Pharyngeal Flap Operation - HIRANO, Akiyoshi (Journal of Japanese Cleft Palate Association, 1993)
In order to investigate the influence of pharyngeal flap operation on maxillary growth, we analyze cephalometric photographs of eleven patients, who were selected as subjects (flap group)among patients undergoing pharyngeal flap at the age of ten years old or less in our department between 1972 through 1986. Sixty five patients undergoing primary repair of cleft palate at our department during the same period were used as control. As a result, there were no differences in values related to maxillary growth, while significant differences between flap group and control were only those related to the pharyngeal cavity or soft palate. These results indicated that pharyngeal flap operation affected only the soft palate, but not directly maxillary growth. However, some patients have severe maxillary hypoplasia after pharyngeal flap operation, so we further compared findings among the flap group. Seven patients of flap group had some secondary repair of cleft palate, such as closure of fistula, and they had maxillary hypoplaside compared with the remaining patients receiving pharyngeal flap alone. When they were compared by dividing them into two groups according to their ages of surgery,5-6 years and 7 years or older, maxillary growth was found to be retarded in the 5-6year group. Since there are so many factors influence maxillary growth after pharyngeal flap, we simulated such effect using a finite element method. When the pharyngeal flap was supposed to be a non-stretching funis, it was implied that pharyngeal flap would affect maxillary growth and induce changes in the nasal tip as well. We could not build up any sound conclusion because of a small number of patients studied. However, although it could be said that pharyngeal flap operation does not always affect maxillary growth even in children of the age of 10 years or less, a possibility of impairment of maxillary growth could not be denied in younger children.